Status of coastal forests of the Northern Sumatra in 2004's tsunami catastrophe) - ONRIZAL ONRIZAL; MASHHOR MANSOR (Society for Indonesian Biodiversity, 2016)
Onrizal, Mansor M. 2015. Status of coastal forests of the Northern Sumatra in 2005 (after 2004's tsunami catastrophe) Biodiversitas 17: 44-54. The first intensive ecological study of coastal vegetation including mangrove, littoral and peat swamp forests after the 2004 tsunami catastrophe in Northern Sumatra was conducted from January to December 2005 where 16 sampling sites along 2960km coastline in Northern Sumatra were selected. In each site, one quadrate of 100 m x 100 m was established and divided into 10 m x 10 m subplots where all standing trees of â‰¥ 2 cm diameter at breast height (DBH) were identified to species level and measured. Overall 54,871 standing trees were recorded in 16 sites comprising 84 species in 65 genera and 37 families. Mangrove trees Rhizophora apiculata and R. mucronata were widely distributed and are dominant in most of the sampling sites. This indicated that these species have stronger resilient compared to other species. The highest value of Shannon-Wiener index of species and Evenness index of speciesÂ was 3.03 and 0.85, respectively. It means that some sites were rich in biodiversity which harbors various species of plants. Subsequently, undisturbed coastal forests including mangroves, littoral forests and peat swamp forests characterized by dense stands, mixed species and structures play an important role in coastal protection against tsunami. Therefore, the coastal vegetation is needed to conserve the biodiversity and to maintain the production capacity as part of sustainable and longlasting vegetation bioshield.